OPTIMALISASI BIAYA OPERASIONAL UMKM AYAM GEPREK MENGGUNAKAN PROGRAM LINEAR METODE SIMPLEKS BERBASIS QM FOR WINDOWS - Muhammad Ariq Syam; Heru Sutejo, Samuel Christiananda, Riyadi Marwan Said, Ahmad Andrian Prayitno, Farhan S. Tuharea (CV. Adiba Aisha Amira, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs), particularly ayam geprek stalls, face significant challenges in managing capital efficiency due to fluctuations in daily operational expenditures. This study aims to minimize the total allocation of daily procurement capital costs at Ayam Geprek MSME through a model restructuring based on consumer purchase volume scenarios, without compromising kitchen inventory safety margins. The method employed is Linear Programming with a Two-Phase Minimization Simplex approach. Primary data collection was conducted via direct observation and structured interviews to formulate three decision variables representing daily wholesale package scenarios, namely a 5-portion package (X1), a 10-portion package (X2), and a 15-portion package (X3). The model also integrates constraint functions for chicken meat capacity (unit: pieces) as well as the minimum daily requirement thresholds for cooking oil (unit: Milliliters) and wheat flour (unit: Grams). Data processing was executed using POM-QM for Windows software under the Linear Programming module. The computational results indicate that maximum daily capital cost efficiency is achieved by focusing solely on serving the wholesale package scenario X3 (15-portion capacity) with 10 daily transactions, while the allocations for packages X1 and X2 are valued at 0. Through this optimal combination, the daily procurement capital cost is successfully minimized to a total of Rp2,610,000 per day to yield a total output of 150 portions, while maintaining a safe backup margin (slack) of 150 pieces of chicken meat in storage, and achieving an optimal absorption of 10,000 mL of cooking oil and 15,000 Grams of wheat flour. This Operations Research approach proves effective as a decision support system for business owners in formulating efficient procurement strategies to secure optimal net profit margins.